2013
DOI: 10.1371/journal.pone.0065482
|View full text |Cite
|
Sign up to set email alerts
|

Role of Electron Microscopy in the Diagnosis of Cadasil Syndrome: A Study of 32 Patients

Abstract: Background and PurposeCerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by NOTCH3 gene mutations that result in vascular smooth muscle cell (VSMC) degeneration. Its distinctive feature by electron microscopy (EM) is granular osmiophilic material (GOM) detected in VSMC indentations and/or the extracellular space close to VSMCs. Reports of the sensitivity of EM in detecting GOM in biopsies from CADASIL patients are contradictory. We present data from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 37 publications
1
24
0
Order By: Relevance
“…Muscle (#1 and #3) or skin (#2) tissue were examined in three affected siblings (Table 1). These data have recently been published (Morroni et al., 2013; Ragno et al., 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Muscle (#1 and #3) or skin (#2) tissue were examined in three affected siblings (Table 1). These data have recently been published (Morroni et al., 2013; Ragno et al., 2012). …”
Section: Methodsmentioning
confidence: 99%
“…At the ultrastructural level, presence of pathognomonic granular osmiophilic material (GOM) deposits confirms the diagnosis with 100% specificity, even without genetic results [10,14,16,17]. Typical GOM, containing Notch3 extracellular domain, is a round granular deposit located in vascular smooth muscle cells (VSMC)/pericyte membrane infoldings.…”
Section: E F G Hmentioning
confidence: 95%
“…Based on our previous studies on CADASIL we have suggested that GOM deposits can be formed on the surface of VSMC/pericytes, can penetrate from the cell into the basement membrane, and then can disperse in the extracellular matrix [7]. Although qualitative or semi-quantitative changes in GOM do not correlate directly with patients' age [10], there are some data indicating a possible relationship of the deposits with progression of histopathological changes in CADASIL. GOM deposits are very early alterations whose development precedes detectable morphological changes in cerebral vessels [4] but not their dysfunction [14].…”
Section: Diverse Ultrastructural Changes In Vessels Of Skin Biopsiesmentioning
confidence: 99%